2020
DOI: 10.1155/2020/3460641
|View full text |Cite
|
Sign up to set email alerts
|

General Issues in Clinical Research of Acupuncture and In Vitro Fertilization

Abstract: In vitro fertilization-embryo transfer (IVF-ET), a well-developed technology, provides the last possibility or hope for infertile women. However, the live birth rate per IVF cycle is still not satisfactory. Acupuncture is a frequently used adjunctive therapy drawing wide attention on improvement of IVF. Although so many randomized controlled trials have been evaluating the effect of acupuncture on IVF in the past 20 years, the exact efficacy of acupuncture on IVF is still controversy mainly because of no conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Insufficient acupuncture dosage in IVF has been a common opinion (78). Some investigators suggested that a clinically valid dosage of acupuncture should be more than six acupuncture sessions and at least choose four to ten (or more) acupuncture points in each session (79). Further study should explore the specific effective dose of acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient acupuncture dosage in IVF has been a common opinion (78). Some investigators suggested that a clinically valid dosage of acupuncture should be more than six acupuncture sessions and at least choose four to ten (or more) acupuncture points in each session (79). Further study should explore the specific effective dose of acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both positive (3,(11)(12)(13)(14)(15)(16)(17) and negative (18-26) effects of acupuncture assisting IVF success were reported. The individualized treatment protocol, different control types, variate acupuncture timing, different searching databases, literature selection criteria, and outcome measures, all potentially contributed to the con icting results (9,27). Since most current trials used the original protocol of Paulus et al(28), the main in uencing factor across studies thereafter might be the types of acupuncture.…”
Section: Introductionmentioning
confidence: 99%